Influência da Nebulosidade na Atenuação Atmosférica na Cidade de Pelotas-RS: Estudo de Caso - Pereira, Rodrigo da Silva; Nunes, André Becker (Ciência e Natura, 2013)
In the study we analyzed the atmospheric attenuation in Pelotas on 20 and 27 February and 21 and 22 June 2013, by calculating the transmittance. The results showed that in both days the incident solar radiation on the surface was attenuated by absorption and scattering of the gas particles suspended in the atmosphere. But, a lot of clouds was paramount to decrease the transmittance of the atmosphere, causing a strong attenuation approximately 81%.